2014
DOI: 10.1177/0269215514545349
|View full text |Cite
|
Sign up to set email alerts
|

What preoperative patient-related factors predict inpatient recovery of physical functioning and length of stay after total hip arthroplasty? A systematic review

Abstract: For the prediction of inpatient recovery of physical functioning no factors with a strong level of evidence were found. For length of stay there was a strong level of evidence for the American Society of Anaesthesiologists score, number of comorbidities, and presence of heart or lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 38 publications
3
24
4
Order By: Relevance
“…These results contrast to those published by Elings et al (2015), which (based on 2 included studies) reported moderate-level evidence for preoperative ADL status, female sex, and BMI; and conflicting evidence for increased age, as prognostic factors of delayed inpatient recovery following THA. Moderate-level evidence indicated no association for ASA PRISMA flow diagram.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results contrast to those published by Elings et al (2015), which (based on 2 included studies) reported moderate-level evidence for preoperative ADL status, female sex, and BMI; and conflicting evidence for increased age, as prognostic factors of delayed inpatient recovery following THA. Moderate-level evidence indicated no association for ASA PRISMA flow diagram.…”
Section: Discussioncontrasting
confidence: 99%
“…Screening could be implemented conjointly with the decision to proceed to surgery, thus maximizing the preoperative window. Simple performance measures may identify patients potentially at risk of delayed recovery, providing the opportunity for preoperative medical and functional optimization, and prompt discharge planning (Elings et al 2015, Oosting et al 2016. Prehabilitation has been demonstrated to improve preoperative function (Swank et al 2011, Clode et al 2018) and may successfully be implemented via telerehabilitation (Doiron-Cadrin et al 2019), thereby capturing patients with reduced access (Westby et al 2010), whilst avoiding significant cost burden to both patients and healthcare organizations (Fusco and Turchetti 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these tools have been proven to be valid and reliable for measuring comorbidities in patients undergoing THA [18][19][20] . The influence of comorbidities on LOS was shown to be limited in our multivariate regression model, which differed from the conclusion drawn from most previous studies 34,35 . We speculated that all of the following reasons may explain the finding in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Although to our knowledge this is the first systematic literature review and meta-analysis where the primary outcome of interest is discharge destination, systematic reviews on patient factors predictive of increased length of hospital stay following TJA have been published [Elings, Shah]. The findings of this review are consistent with those reported patient risk factors associated with longer length of stay, including female gender, older age, increased comorbidities and higher BMI [31,32].…”
Section: Patient Reported Outcome Measuressupporting
confidence: 76%